Production of maleylpyruvate and fumarylpyruvate - LIU Dong-qi; LIU Hong; ZHOU Ning-yi (浙江大学学报. 农业与生命科学版)
Gentisate 1,2-dioxygenase (GDO, EC1.14.13) from Klebsiella pneumoniae M5a1 successfully converted gentisate to maleylpyruvate. This biotransformation was performed by using genetically engineered E. coli strain carrying a gene encoding gentisate 1,2-dioxygenase, and the maleylpyruvate synthesized by this enzyme attained a purity as high as 97.7%. Purity of fumarylpyruvate obtained by acidifying the resulting maleylpyruvate with meta-phosphoric acid was 96.4%. This study thus established a method which is suitable for the production of maleylpyruvate and fumarylpyruvate.